Investigations of the antimicrobial activity of aminomethanesulfonic acids against strains of Staphylococcus aureus with different antimicrobial susceptibility - Hrydina, T. L.; Khoma, R. Ye.; Ennan, A. A.-A.; Fedchuk, A. S.; Hruzevskyi, O. A. (Zaporozhye Medical Journal, 2019)
One of the tasks of the WHO strategy against development of antibiotic resistance in microorganisms is the searching for new compounds with antimicrobial activity to develop new antimicrobial medicines. The aim of this study was to determine the inhibitory effect of aminosulfonic acid (AMSA) and its new derivatives such as N-methyl-(MeAMSA), N-(2-hydroxyethyl)-(HEAMSA), N-benzyl-(BnAMSA), N-(tert-butyl)-(t-BuAMSA), 4-(N-phenylaminomethyl)phenyl (PhAMPhAMSA) on the growth of Staphylococcus aureus strains with different antimicrobial susceptibility. Materials and methods. The method of serial dilution was used in the study. The chemical compounds were dissolved in DMSO (a final concentration of 1%). Then dilutions of the compounds were performed using liquid Mueller-Hinton medium to final concentrations of 5 mM and 10 m×M. The results were assessed using a Densi-La-Meter after 18-20 hours of incubation at 37 °C. Sulfanilamide was used as a reference preparation. Results. AMSA suppressed the growth of all tested strains regardless of their antibiotic resistance profiles even more than sulfanilamide. MeAMSA inhibited the growth of S. aureus ATCC 25923 and S. aureus 2781 strains more than the reference preparation, but less than AMSA. No inhibitory effect was observed on the antibiotic resistant S. aureus Kunda strain. Compounds of HEAMSA, t-BuAMSA, BnAMSA stably inhibited the growth of all strains tested. These compounds suppressed the growth of S. aureus ATCC 25923 and S. aureus Kunda strains more than sulfanilamide. However, the reference preparation exhibited greater S. aureus 2781 growth inhibition than investigated preparations. Compound PhAMPhAMSA did not show antimicrobial activity. Conclusions. Aminomethanesulfonic acid derivatives suppressed the growth of Staphylococcus aureus strains with different antimicrobial susceptibility and their antimicrobial activity was higher than that of sulfanilamide. Further study of these compounds efficacy on different types of microorganisms can be considered promising for the development of new antimicrobial agents. It would also be appropriate to study the combined use of these substances with antibiotics.